A model for identifying owner’s needs in the building life cycle - Alshubbak, Ali; Pellicer, Eugenio; Catalá, Joaquín; Teixeira, José M. C. (Journal of Civil Engineering and Management, 2015)
Building life cycle is a process which covers not only the construction phase but also the feasibility, the design and the operation phases. Identifying the owner’s needs in all phases of this process is of paramount importance for achieving satisfactory results for the building project. Additionally, the owner’s needs should be fulfilled by the work scope of every stakeholder involved in the project. Nevertheless, these needs are not always adequately considered in building projects. Thus, the purpose of the research reported in this paper has been to develop a model that allows for the identification of the owner’s needs in all phases of the building life cycle. The article presents a six level classification system for the information required in the project and a two-dimensional model that maps the life cycle and the logical actions to be undertaken in each phase. The model has been corroborated and improved by applying the Delphi technique to a panel of ten experts in two rounds. The practical use of the model is through the systematic application of a series of questionnaires built upon the information classification system for determining the owner’s needs. The paper details the operation phase of the model as an illustrative example and a case study on a residential building project of twelve apartments in Spain.